Mentions of complainant sexual arousal in Canadian criminal sexual assault cases. - Vandervoort, Mariève; Forget, Audrey-Anne; Potvin, Christen; Samosh, Jonathan; Dewar, Michelle (Canadian Journal of Human Sexuality, 2025)
Involuntary sexual arousal can be experienced by victims during sexual assault. The misconception that sexual arousal equates to a victim's consent is a "rape myth," sometimes used to deny the occurrence of an assault, including in criminal trials. The goals of this scoping review were threefold: (a) to assess if complainant sexual arousal was discussed in Canadian criminal sexual assault cases, and if so, what signs of sexual arousal; (b) how sexual arousal was interpreted by legal actors, and (c) whether this contributed to case outcomes. Canadian legal databases CanLII, LexisNexis, and Westlaw were used to extract and screen 4,301 legal materials from Canadian sexual assault trials. Mentions of complainant sexual arousal, including moaning, hip movement, genital warmth, vaginal lubrication, and penile erection, were found in 13 cases, 12 of which involved female complainants and one case involving a male complainant. Content analysis of these cases revealed that signs of complainant sexual arousal were considered relevant evidence to ground the accused's defences of "mistaken belief in consent" in all cases. The findings of this review emphasize the need to distinguish between sexual arousal and sexual consent and the risks associated with their confusion in legal contexts. Results support the promotion of standardized sexual education, including comprehensive information about consent. Additionally, they highlight the need for legal protections against the misuse of evidence related to complainant arousal to ensure criminal legal processes function with truth, fairness, and justice for all.